A review of FM services for enhancing and provisioning of optimal quality municipal services for local government in Malaysia - Bello, Muhammad Umar; Martin, David; Kasim, Rozilah; Ahmad Aliyu, Aliyu (American Scientific Publishers, 2017)
Facilities Management services are very significant for effective and efficient service delivery. Facilities Management services is not just to optimize running costs of buildings, but to raise efficiency of the management of space and related assets for people and processes, in order that the mission and goals of the organization may be achieved at the best combination of efficiency and cost. This study reviewed the FM Services for the enhancing and provisioning of optimal quality municipal services of local government in Malaysia. This study shows that FM services are paramount for effective service delivery most especially in local government. But FM services are not much recognized in Malaysia which makes many local government service deliveries inefficient. Indeed, in recent years, the series of services covered within the context of facilities management has been visible as more complex, facilities management has turned into the main operational and technical functions of an organisations. Materials and methods were carried out using secondary data and analyses critically to come up with reliable results. A way forward is that local government authorities should embark on using the FM services by employing staffs that are FM professionals in terms of in-house service delivery and outsourcing for the services that are detriment for the development of local communities. FM and community awareness programs in developmental project and in terms of decision making for any services to be rendered to the populace, local authorities should make sufficient fiscal effort to obtain all the resources that are potentially available to them and accountability should be employ for judicious utilization of financial resources. The research concludes by recommending that Malaysian local authorities should be concerned with their main constitutional responsibilities of provisioning of effective and efficient services based on the needs and wants of the local community through FM services.